Role of Organizational Culture on Knowledge Sharing Practices among Employees in Leather Industry - PRIYA, R.; ADAIKALAM, J. JOHN (International Journal of Psychosocial Rehabilitation, 2020)
Even though SMEs play a vital role to reduce unemployment, shortage of capital, organizational culture and management talents makes difficult to implement knowledge management practices in SMEs. India is the second largest leather producer in the world and it is accounted about 13% of leather production. Need for skilled and talented workforce to leather industry turns the researcher to study about the knowledge sharing methods in this industry. This paper presents literature review on organizational culture and knowledge sharing in small and medium sized enterprises. Being the largest producers and skill oriented industry, it is crucial to study about knowledge sharing methods adopted by these employees and how far organizational culture is influencing the knowledge sharing process. Samples are collected from small and medium sized leather companies in and around Chromepet, Chennai through questionnaire. Out of 100 questionnaires administered, 92 were collected and analyzed using SPSS software. The study reveals that organizational culture influences the tacit knowledge sharing as well as explicit knowledge sharing.